2015
DOI: 10.18632/oncotarget.4154
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA H19 promotes epithelial to mesenchymal transition by functioning as miRNA sponges in colorectal cancer

Abstract: Recently, the long non-coding RNA (lncRNA) H19 has been identified as an oncogenic gene in multiple cancer types and elevated expression of H19 was tightly linked to tumorigenesis and cancer progression. However, the molecular basis for this observation has not been characterized in colorectal cancer (CRC) especially during epithelial to mesenchymal transition (EMT) progression. In our studies, H19 was characterized as a novel regulator of EMT in CRC. We found that H19 was highly expressed in mesenchymal-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
443
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(460 citation statements)
references
References 48 publications
14
443
3
Order By: Relevance
“…4 Zhuang et al 24 cells. 28 In this study, SNHG7 modulated miR-193b availability by acting as a molecular sponge, which down-regulated the miR-193b levels to enhance its target gene FAIM2-induced tumour survival,…”
Section: Discussionmentioning
confidence: 82%
“…4 Zhuang et al 24 cells. 28 In this study, SNHG7 modulated miR-193b availability by acting as a molecular sponge, which down-regulated the miR-193b levels to enhance its target gene FAIM2-induced tumour survival,…”
Section: Discussionmentioning
confidence: 82%
“…LncRNAs can also function as a competing endogenous RNA to sponge microRNAs (12)(13)(14). For example, the lncRNA H19 promotes EMT by functioning as a miRNA sponge to miR-138 and miR-200a in colorectal cancer (15). Therefore, by interacting with specific miRNAs, lncRNAs can play an important role in cancer development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…While, recently studies identified several lncRNAs as valuable diagnosis and prognosis biomarkers in cancers and other types of complex diseases, such as lncRNA-p53, H19, MALAT1 [16,32,33]. In this study, besides differential expression analysis of lncRNA, miRNA and mRNA, we also drew our attention to the prognosis significance of DEL.…”
Section: Discussionmentioning
confidence: 96%
“…And thus, the three types of RNA form the lncRNA-miRNA-m RNA ceRNA network, which should play important roles in many types of diseases. Liang and collages [16] illustrated that lncRNA H19 promotes epithelial to mesenchymal (ETM) transition by acting as miRNAs sponge in colorectal cancer. Endogenous miRNA sponge lincRNA-RoR regulates Oct4, Nanog, and Sox2 in human embryonic stem cell self-renewal [17].…”
Section: Introductionmentioning
confidence: 99%